Peran Komunikasi dalam Konteks Hubungan Keluarga - Mohamad Permana, Rangga Saptya; Suzan, Nessa (PT. RANESS MEDIA RANCAGE, 2023)
Family has a significant impact on the features that determine our interactions with the environment. Mary Anne Fitzpatrick and her colleagues have produced a number of studies and hypotheses concerning family ties. The research findings and theory of Fitzpatrick inform us on the various types of families, their peculiarities, and the effect of these differences on how they communicate. Hence, the author is interested in examining the role of communication within the context of family relationships and attempts to incorporate references within the context of family communication. The goal of this study is to determine the extent to which communication plays a role in family relationships, which is derived from numerous earlier conceptions regarding relationships and families. In this paper, the author studies the roles of communication within the setting of family relations using the literature review approach, with three primary references serving as the major basis for the study. In addition to these three references, the author complements the study materials with other reading pertaining to discussions of family relationships and communication. According to studies employing the concepts of family relationships and communication, communication plays a crucial role in family interactions. Communication has an essential part in the formation of a family's social reality. Relationships and communication patterns within the family are heavily influenced by two communication activities, namely conversation and conformity, which also determine family communication patterns.